2022
DOI: 10.3390/ma15238475
|View full text |Cite
|
Sign up to set email alerts
|

Frontiers of Hydroxyapatite Composites in Bionic Bone Tissue Engineering

Abstract: Bone defects caused by various factors may cause morphological and functional disorders that can seriously affect patient’s quality of life. Autologous bone grafting is morbid, involves numerous complications, and provides limited volume at donor site. Hence, tissue-engineered bone is a better alternative for repair of bone defects and for promoting a patient’s functional recovery. Besides good biocompatibility, scaffolding materials represented by hydroxyapatite (HA) composites in tissue-engineered bone also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 217 publications
0
11
0
Order By: Relevance
“…Hydroxyapatite (HA, Ca 10 (PO 4 ) 6 (OH) 2 ) exhibits structure and composition similar to that of natural apatite found in bone tissues and, owing to its high mechanical strength and biocompatibility, it is widely used as a scaffold material for bone TE. However, HA may have several drawbacks as a scaffold material, including a mismatch between the degradation rate and new bone formation as well as the low porosity and plasticity of the scaffolds, which impede its widespread use [ 95 , 96 ].…”
Section: Electrospun Inorganic Nanofibers For Tissue Engineering Appl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxyapatite (HA, Ca 10 (PO 4 ) 6 (OH) 2 ) exhibits structure and composition similar to that of natural apatite found in bone tissues and, owing to its high mechanical strength and biocompatibility, it is widely used as a scaffold material for bone TE. However, HA may have several drawbacks as a scaffold material, including a mismatch between the degradation rate and new bone formation as well as the low porosity and plasticity of the scaffolds, which impede its widespread use [ 95 , 96 ].…”
Section: Electrospun Inorganic Nanofibers For Tissue Engineering Appl...mentioning
confidence: 99%
“…For bone TE, HA composites have been shown to exhibit compressive strength between 2 to 230 MPa and modulus of elasticity in the range of 0.05 to 30 GPa, thereby matching the mechanical properties of bone tissues. In addition, the scaffolds displaying pore sizes above 50 μm and degradation period between 2 to 6 months have been shown to facilitate cellular infiltration and angiogenesis for bone TE [ 95 ]. As mentioned above, despite good potential of hybrid scaffolds solely fabricated by using natural/synthetic polymers, additional candidates, such as inorganic NMs may be harnessed to further ameliorate the limitations associated with these scaffolds as well as confer additional bioactivity to scaffolds.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Considering the absorbability, it was observed that a fast resorbing calcium phosphate bone substitute was directing the structural alterations of the host bone to vital bone tissue in a radiographical study [ 5 ]. It was stated that the optimal degradation rate of the scaffold is similar to the rate of osteogenesis [ 6 ]. Thus, the scaffold’s structure would be replaced by new bone.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, bioactive scaffolds avoid the drawbacks of traditional bone repair procedures, such as lack of bone cells and immune rejection, which can considerably reduce the patient’s suffering from bone diseases ( O'Brien, 2011 ; Delloye et al, 2007 ). The ideal scaffold is also required to have superior osteoinductivity, matching the new bone production rate’s degradation rate, mechanical strength compatible with the original bone, etc., ( Lee et al, 2022 ; Shi et al, 2022 ). Generally, bone tissue engineering scaffolds are available in four categories: natural polymers, synthetic polymers, bioceramic materials, and composite biomaterials ( Boos et al, 2010 ; Lee et al, 2022 ; O'Brien, 2011 ; Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%